Unlocking the secrets of glucose metabolism reprogramming: the role in pulmonary diseases - Li, Zhen; Chen, Shuo-Xuan; Jiang, Shuai; Yang, Yi-Nong; Yan, Xi-Chan (Frontiers in Pharmacology, 2025)
Metabolic reprogramming is the process by which cells adapt to different patterns of energy metabolism in response to the demands of the microenvironment for energy and biological macromolecules. Glucose serves as the primary energy source for cellular survival, and its metabolic pathways are intricately associated with cellular functional states. Recent studies have demonstrated that alterations in glucose metabolism, along with non-metabolic functions of metabolic enzymes and metabolites, play crucial roles in the development and progression of lung diseases under inflammatory conditions. This review summarizes the regulatory mechanisms of glucose metabolism across various pulmonary disorders and discusses the non-metabolic functions of glycolytic enzymes and metabolites in relation to disease pathogenesis. We aim to shine new light on the diagnosis and treatment of lung disease.